Highlight article: Estradiol and NADPH oxidase crosstalk regulates responses to high fat feeding in female mice. Issue 10 (July 2019) - Ronis, Martin J; Blackburn, Michael L; Shankar, Kartik; Ferguson, Matthew; Cleves, Mario A; Badger, Thomas M
We previously demonstrated protection against high fat-induced obesity in female but not male p47 phox −/− mice lacking NADPH oxidase NOX1/2 activity. To test the role of estradiol (E2)-NOX crosstalk in development of this sexually dimorphic phenotype, we fed diets containing 42% fat/0.5% cholesterol to intact and ovariectomized wild type female C57BL/6 mice and female p47 phox −/− mice and to ovariectomized mice where the diet was supplemented with an 1 mg/kg 17β estradiol (E2) for 12 weeks from PND28. Weight gain, gonadal fat pad weight, serum leptin and adiponectin, and adipose tissue inflammation were greater in intact wild type vs. p47 mice ( P  < 0.05). Genotype effects on body weight/fat mass were abolished after ovariectomized and restored in OVX + E2 mice ( P  < 0.05). The mRNA of downstream PPARγ targets CD36, lipoprotein lipase, and leptin was higher in intact wild type vs. p47 phox −/− mice mice ( P  < 0.05). Likewise, intact high fat-fed wild type mice had higher expression of the cytokine Mcp1 ; the pyroptosis marker Nirp3 and matrix remodeling and fibrosis markers Mmp2, Col1A1, and Col6a3 mRNAs ( P  < 0.05). These genotype effects were reversed and restored by ovariectomized and OVX + E2, respectively ( P  < 0.05). These data suggest that triglyceride accumulation in adipose tissue and development of adipose tissue injury in response to feeding diets high in fat and cholesterol is regulated by the balance between NOX-dependent reactive oxygen species signaling and E2-signaling during development. Loss of estrogens post menopause may increase the risk of obesity and metabolic syndrome as the result disinhibition of reactive oxygen species signaling. Impact statement: Estrogens are known to regulate body composition. In addition, reactive oxygen species (ROS) produced by the action of NADPH oxidase (NOX) enzymes have been linked to obesity development. We examined development of obesity and adipose tissue injury in response to feeding "Western" diets high in fat and cholesterol in intact, ovariectomized (OVX), and estrogen-replaced (OVX + E2) wild type and p47 phox−/− female mice where NOX2 activity is inhibited. Weight gain, gonadal fat pad weight, and adipose tissue inflammation were greater in intact WT vs. p47 phox−/− mice. Genotype effects on body weight/fat mass were abolished after OVX and restored in OVX + E2 mice. These data indicate adipose tissue responses to feeding the "Western" diet is regulated by negative cross-talk between NOX-dependent ROS signaling and E2-signaling during development. Loss of estrogens post menopause may increase the risk of obesity and metabolic syndrome as the result disinhibition of ROS signaling.